Designing an Information System for Determining Restitution on Dedicated Internet Bills - Rica Fardilah; Verdi Yasin; Tomi Loveri (Journal of Information System, Informatics and Computing, 2022)
Internet Dedicated bill payment process is determined by the operational achievement of its internet connection. If the internet service provided by the ISP (Internet Service Provider) is not in accordance with the SLA (Service Level Agreement), it means that there is a disturbance in the internet connection and the payment will automatically have an impact on the imposition of restitution. To support the decision-making process whether the claim is subject to restitution or not, it is necessary to make decisions that are fast, targeted and accountable to be the main focus. This research was conducted to change the determination of restitution on Internet Dedicated bills conventionally with Ms. Excel became a computerized database. With the development of the system analyzed using the waterfall method. The result of this research is a web-based application for determining the value of restitution.